Reproductive technology: a critical analysis of theological responses in christianity and Islam - Ishak, Mohd. Shuhaimi; Haneef, Sayed Sikandar Shah (Blackwell Publishing Ltd., 2014)
Reproductive medical technology has revolutionized the natural order of human procreation. Accordingly, some have celebrated its advent as a new and liberating determinant of kinship at the global level and advocate it as a right to reproductive health while others have frowned upon it as a vehicle for “guiltless exchange of sexual fluid” and commodification of human gametes. Religious voices from both Christianity and Islam range from unthinking adoption to restrictive use. While utilizing this technology to enable the married couple to have children through the use of their own sexual material is welcome, the use of third party, surrogacy, and reproductive cloning are not in keeping with the sacrosanct principles of kinship, procreation through licit sexual intercourse, and social cohesiveness for building a cohesive family as uphold by both Christianity and Islam. To examine such larger issues emanating from these new ways of human procreation, beyond the question of legality, is a point which legal scholars in both Christianity and Islam, when issuing religious decrees, have not anticipated sufficiently. The article proposes to be an attempt to that end through a qualitative critical content analysis of selected literature written on the subject.